PERILAKU DISFUNGSIONAL AUDITOR TERHADAP KUALITAS AUDIT - Istanti, Sri Layla Wahyu (Potensio, 2009)
Abstract In order to achieve accountability and transparency, the au- dit function is very essential. The audit results will provide feedback to all parties related to the company or organiza- tion. Audit opinion is not received a positive response be- cause of the possibility of behavioral deviation by an auditor in the audit process. Dysfunctional behavior includes audi- tors Underreporting of time, premature sign-off (PMSO) and Altering/replacing of the audit procedure. This behavior is caused by the locus of control (locus of control), personal performance level of employees, the desire to stop working, self-esteem in terms of ambition, and commitment to the organization. To overcome the impact of this behavior should KAP strict supervision of all auditors, and improve commu- nication within the audit team.Keyword: Dysfunctional behavior auditors, Audit quality